AKTIVITAS MINYAK ATSIRI BUNGA LILY (Lilium auratum) TERHADAP BAKTERI Salmonella typhi - Dwi Rizki Febrianti; Siska Musiam; Dani Kurniawan (Jurnal Komunitas Farmasi Nasional, 2021)
Salmonella typhi infection caused by Salmonella typhi attacks the intestinal tract and breeds there. Types of raw food and seafood can be contaminated by this bacteria. The risk of infection is high in patients with congenital inflammatory bowel disease and immune problems. The potential of natural materials such as lilies has not been explored much. The components of lily essential oil compounds contain benzaldehyde, linalool, cement, borneol and osimen which can react with bacterial cell wall components causing damage to bacterial cell walls. The purpose of this study was to determine the potential of lily flower essential oil (Lilium auratum) in inhibiting the growth of salmonella typhi bacteria. Using with a concentration of 10%, 30%, 50% and 70%. The results of the test using the disc method showed that lily essential oil was able to inhibit bacteria with inhibition zones of 10% (13.83 mm), 30% (13.25 mm), 50% (15.05 mm) and 70% (15.26 mm) with a strong category.